2008
DOI: 10.1590/s1415-790x2008000100015
|View full text |Cite
|
Sign up to set email alerts
|

Associações entre atividade física, índice de massa corporal e comportamentos sedentários em adolescentes

Abstract: OBJETIVO: Este estudo teve como objetivo determinar a associação do índice de massa corporal (IMC) com os níveis de atividade física (AF) e comportamentos sedentários (assistir TV, usar computador ou jogar videogames) em adolescentes de escolas públicas do Estado de Santa Catarina (15-19 anos; n = 5.028). MÉTODOS: As informações foram coletadas por meio de questionário desenvolvido e validado para adolescentes. Foram considerados insuficientemente ativos, os jovens que não acumulavam pelo menos 300 minutos/sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
29
1
37

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 27 publications
8
29
1
37
Order By: Relevance
“…In ten studies, the sample was school-based 16,17,18,19,20,21,22,23,24,25 and four included workers 26,27,28,29 . The sample size ranged from 160 individuals 30 to 54,369 8 , while the majority of the studies (38) included more than a thousand subjects, and only two included fewer than five hundred 30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…In ten studies, the sample was school-based 16,17,18,19,20,21,22,23,24,25 and four included workers 26,27,28,29 . The sample size ranged from 160 individuals 30 to 54,369 8 , while the majority of the studies (38) included more than a thousand subjects, and only two included fewer than five hundred 30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding excess body fat, the result found in the present study agrees with the findings of Adami and Vasconcelos 26 in which there was also a lower chance of excess body fat in girls. However, a study by Silva et al 4 found that girls were more likely to present excess body fat. With the results found, it is observed that the associations between being of a given sex and having or not being overweight and/or sleeping inadequately are not yet conclusive.…”
Section: Discussionmentioning
confidence: 96%
“…In Brazil, in the period 2008-2009, the Family Budget Survey (POF) estimated a prevalence of overweight and obesity for the age group of 10 to 19 years of age as 21.7% and 5.1% for boys, and 19.4% and 4.0% for girls, respectively 2 . The subgroups of adolescents with higher frequencies of overweight/obesity were boys, students of the public school system, who had low economic status and lower maternal schooling 3,4 .…”
mentioning
confidence: 99%
“…41 Nesta revisão, verificou-se que os rapazes se encontram em EMC mais avançados em relação às moças. Esses resultados vão ao encontro de outros estudos nacionais [42][43][44] e internacionais 9,45 . Segundo Gonçalves (2007) 46 , tal fato pode ser explicado por questões socioculturais, pois rapazes possuem maiores incentivos tanto sociais quanto familiares para engajar-se em AF.…”
Section: Discussionunclassified
“…Foi identificada associação negativa entre EMC e estado nutricional, estando os estágios iniciais associados ao risco de sobrepeso/obesidade 43,56 . Entretanto, o que ainda não está claro é se o sobrepeso que dificulta a prática habitual de AF ou vice-versa 33 .…”
Section: Discussionunclassified